Detection of two zoonotic pathogens, Seoul orthohantavirus and pathogenic Leptospira, in rats of Bamako, Mali (2021−2023) - J. Garona; A. Berard; C. Tatard; A. Kwasiborski; P. Gauthier; S. Ag Atteynine; V. Hourdel; A. Eusebe; C. Diagne; V. Caro; C. Brouat; N. Charbonnel; et al. (One Health)
Seoul orthohantavirus (SEOV) and pathogenic leptospires, two zoonotic agents causing similar symptoms in humans, were investigated in rat populations across several neighborhoods in Bamako, Mali. SEOV seroprevalence in brown rats (Rattus norvegicus) reached 14.8 %, while no infection was detected in black rats (Rattus rattus). Pathogenic leptospires were found in 8.7 % of brown rats, with significant inter-neighborhood variations, while only one black rat tested positive. Viral genetic analyses suggested that SEOV strains circulating in Bamako may result from a reassortment between two SEOV lineages. These findings highlight the widespread distribution of SEOV and the localized presence of pathogenic leptospires in Bamako, emphasizing the role of brown rats as reservoirs. These results can guide municipal authorities in implementing rodent control and prevention strategies to mitigate associated public health risks in Bamako.